The renal damage and mechanisms relevant to antitumoral drugs - Tang, Jiyu; Yang, Nan; Pan, Shujun; Ren, Peiyao; Chen, Maosheng; Jin, Juan; He, Qiang; Zeng, Yuqun (Frontiers in Oncology, 2023)
Over the past few decades, significant progress has been made in the development of drugs to combat cancer. It is unfortunate that these drugs can also lead to various kidney injuries and imbalances in electrolyte levels. Nephrotoxicity caused by chemotherapy drugs can impact different parts of the kidneys, including the glomeruli, renal tubules, interstitium, or renal microvessels. Despite the existing knowledge, our understanding of the mechanisms underlying the renal damage caused by antitumoral drugs remains incomplete. In this review, we aim to provide a comprehensive overview of the specific types of kidney injury and the mechanisms responsible for the drug-mediated renal damage, and briefly discuss possible prevention and treatment measures. Sensitive blood and urine biomarkers can provide clinicians with more information about kidney injury detection and reference value for subsequent treatment options. In addition, we emphasize that both oncologists and nephrologists have a responsibility to remain vigilant against the potential nephrotoxicity of the drugs. It's crucial for experts in both fields to collaborate in early detection, monitoring and prevention of kidney damage.